Lattice-boltzmann method applied to the pattern formation on periodic surface structures generated by multiline nanosecond laser (2014)
We simulated the pattern formation on silicon surfaces. For this purpose, we used Lattice-Boltzmann method assuming two non-ideal interacting fluids using a lattice velocity D2Q9. The experiment was carried out with a multiline (1064, 532 and 355 nm) Nd: YAG pulsed laser that employs an energy range from 310 to 3100 J on a surface p-type monocrystalline silicon oriented in the direction [111]. The whole system was subjected to argon gas blowing which is key in pattern formation. Computer simulation reproduces the overall behavior of the experimental geometric patterns expressed in oblique parallel ripples quite well.